Neural substrates of treatment-resistant schizophrenia and the response to clozapine: A structural MRI study in a clinical setting - Yuto Masumo; Nobuhisa Kanahara; Yuji Otsuka; Yusuke Sudo; Teruyuki Ishii; Hirotaka Sato; Keita Idemoto; Hiroshi Komatsu; Yuko Fujita; Yasunori Oda; Tomihisa Niitsu; Yoshiyuki Hirano; et al. (PLoS ONE, 2026)
Background Predicting the responsiveness to clozapine among individuals with treatment-resistant schizophrenia (TRS) is difficult. A candidate predictor of clozapine response is the length of time prior to the introduction of clozapine treatment. The relationship between this measure and structural MRI findings has not been established. Patients and methods We compared the cortical-volume ratio between patients with TRS (n = 40 including 20 clozapine-treated patients) and non-TRS patients with schizophrenia (n = 64) and between each of these patient groups and healthy controls (HCs). We then investigated brain regions related to both responsiveness to clozapine and the duration between the TRS designation and the introduction of clozapine. Results The three-group comparison revealed that compared to the HCs, both patient groups had significantly lower cortical-volume ratios in widespread brain regions. However, there was no significant difference in the brain regions between the TRS and non-TRS groups: compared to the non-TRS group, the TRS group showed smaller volumes in a wider range of brain regions only at the uncorrected level. The correlational analysis of regions related to clozapine responsiveness did not identify any region that survived the correction for multiple comparisons. No relationship between any cortical region and the length of time prior to clozapine introduction was observed. Conclusion Overall, these results failed to identify the cortical region responsible for the treatment response to clozapine. The lack of correlations between the length of time prior to clozapine introduction and cortical regions might have been derived by insufficient statistical power, thus necessitating further research.